Ethnomathematical Exploration of The Admission Schedule For The Five Timely Prayers - Niswatin, Indah Nur Wahidatun; lutfi, Lutfiyah; Panglipur, Indah Rahayu (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2025)
An introduction to the practice of the five daily prayers in islam has become an integral part of the lives of muslims worldwide. The adhan, the call to prayer, is recited five times daily, marking the designated, times for worship. However, beyond its spiritual aspect, the adhan schedule also reflects a fascinating mathematical system, influencing and reflecting the relationship between time, geometry,and the daily lives of muslims. An ethnomathematical exploration of the adhan schedule for the five daily prayers from an ethnomathematics in the learning process can enrich teaching materials by connecting these aspects to students’ cultures. The method used in this study is a qualitative approach with an ethnographic approach, where data is collected through observation, interviews, and documentation